Development of Powtoon-Assisted Learning Media to Improve Students' Critical Thinking Skills in Science Subjects - Rocha Linda; Achmad Bukhori; Andi Priyolistiyanto (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to develop Powtoon-assisted learning media to improve critical thinking skills among eighth-grade science subjects at Junior High School 1 BPR Ranau Tengah. Methodology: This qualitative study uses Powtoon software to design instructional media. Data were collected using interview guides, observation sheets, and documentation. Miles and Huberman's interactive model was applied to the data analysis. Primary data were collected through field interviews and classroom observations; Secondary data is obtained from books, journals, and online sources. Main Findings: Powtoon-assisted learning media significantly increased student engagement, understanding, and motivation in science learning. Students exhibit better critical thinking skills, especially in analyzing, evaluating, and articulating ideas logically. Teachers reported increased student participation and enthusiasm. Despite technical challenges such as internet access and device limitations, the overall response to Powtoon media was positive and indicated a significant improvement in learning effectiveness. Novelty/Originality of this Study: This study introduces Powtoon as an innovative tool specifically applied to enhance critical thinking in science at the junior high school level. Unlike previous research that focused on general understanding or motivation, this study highlights Powtoon's role in developing high-level thinking. It contributes to the practice of digital education by bridging animation-based media with the development of cognitive skills.